THE ROLE OF PENTAHELIX IN TOURISM DEVELOPMENT IN BINJAI CITY - Januardi; Tengku Irmayani; Nurman Achmad (OPINI: Journal of Communication and Social Science, 2025)
Binjai City is a region in North Sumatra with significant tourism potential. However, tourism development in Binjai City still faces several challenges. In this context, pentahelix collaboration is crucial to promote sustainable and competitive tourism development. This study aims to explore the roles of the five main actors in the pentahelix model of tourism development and identify the challenges facing tourism development in Binjai City. This study employed a qualitative approach and was conducted in Binjai City, utilizing data collection techniques through interviews, observation, and documentation. The results indicate that the government acts as a facilitator and regulator, academics contribute through research and policy recommendations, business actors strengthen the tourism sector, the media plays a role in promotion and image building, and communities play a role in preserving culture and encouraging public participation. However, obstacles remain, including limitations in regulations, infrastructure, promotion, budgets, human resources, and local community capacity. Therefore, tourism development in Binjai City requires stronger synergy between the pentahelix sectors to create an inclusive, innovative, and sustainable tourism ecosystem.